Biochemical characterization of the chloroplastic β-carbonic anhydrase from Flaveria bidentis (L.) "Kuntze". (August 2014) - Dathan, Nina A.; Alterio, Vincenzo; Troiano, Elisa; Vullo, Daniela; Ludwig, Martha; De Simone, Giuseppina; Supuran, Claudiu T.; Monti, Simona M.
Abstract C3 and C4 plant carbonic anhydrases (CAs) are zinc-enzymes that catalyze the reversible hydration of CO2. They are sub-divided in three classes: α, β and γ, being distributed between both photosynthetic subtypes. The C4 dicotyledon species Flaveria bidentis (L.) "Kuntze" contains a small gene family encoding three distinct β-CAs, named FbiCA1, FbiCA2 and FbiCA3. We have expressed and purified recombinant FbiCA1, which is localized in the chloroplast where it is thought to play a role in lipid biosynthesis and antioxidant activity, and biochemically characterized it by spectroscopic and inhibition experiments. FbiCA1 is a compact octameric protein that is moderately inhibited by carboxylate molecules. Surprisingly, pyruvate, but not lactate, did not inhibit FbiCA1 at concentrations up to 10 mM, suggesting that its capacity to tolerate high pyruvate concentration reflects the high concentration of pyruvate in the chloroplasts of bundle-sheath and mesophyll cells involved in C4 photosynthesis.